The School Principal's Management Strategies for Improving Students' Academic Achievement - Taufik Azhar Manurung; Dwi Meutia Hasni; Muhamad Qomarudinul Huda; Nurhalimah (DAAR EL-IDARAH: Journal of Islamic Education Management, 2026)
This research was conducted at SMAN 1 Tanjungbalai, the type of research carried out was qualitative research methods. This research approach uses a descriptive approach. The subjects in this study were principals, teachers/employees, and students. In collecting data, researchers used observation, interview, and documentation methods, while data analysis was carried out by means of data reduction, data presentation, and triangulation. This study aims to find out how the planning, organizing, implementation, and supervision are carried out by school principals and to find out how the process of implementing and evaluating school principals in improving student achievement at SMAN 1 Tanjungbalai. The results of the research carried out are: the management function carried out by the principal is to use planning, organizing, implementing, and supervising. Furthermore, the strategy carried out by the principal is to plan programs for students starting from the lesson plans and extracurricular activities, while for teachers to make guided activities and guidance. In the process of implementation, the principal determines school policies, motivates educators and staff performance personnel, allocates human resources, and develops a culture of local school wisdom. Then in the evaluation process the principal monitors all the results of activities that have been carried out from the predetermined plans, measures individual and school performance, takes corrective steps. The strategy also contributed to strengthening the values of Islamic Religious Education